Training for endurance and strength: Lessons from cell signaling - Baar, K. (Medicine & Science in Sports & Exercise, 2006)
The classic work of Hickson demonstrated that training for both strength and endurance at the same time results in less adaptation compared with training for either one alone: this has been described as the concurrent training effect. Generally, resistance exercise results in an increase in muscle mass, and endurance exercise results in an increase in muscle capillary density, mitochondrial protein, fatty acid-oxidation enzymes, and more metabolically efficient forms of contractile and regulatory proteins. In the 25 yr since Hickson's initial description, there have been a number of important advances in the understanding of the molecular regulation of muscle's adaptation to exercise that may enable explanation of this phenomenon at the molecular level. As will be described in depth in the following four papers, two serine/threonine protein kinases in particular play a particularly important role in this process. Protein kinase B/Akt can both activate protein synthesis and decrease protein breakdown, thus leading to hypertrophy, and AMP-activated protein kinase can increase mitochondrial protein, glucose transport, and a number of other factors that result in an endurance phenotype. Not only are PKB and AMPK central to the generation of the resistance and endurance phenotypes, they also block each other's downstream signaling. The consequence of these interactions is a direct molecular blockade hindering the development of the concurrent training phenotype. A better understanding of the activation of these molecular pathways after exercise and how they interact will allow development of better training programs to maximize both strength and endurance.